The Road to Armageddon Paraguay Versus the Triple Alliance, 1866-70 - Whigham, Thomas L. (Latin American & Caribbean Studies, 2017)
In 1864 the capture of Brazilian steamer the Marquês de Olinda initiated South America's most significant war. Thousands of Brazilian, Argentine, and Uruguayan soldiers engaged in a protracted siege of Paraguay, leaving the Paraguayan economy and population devastated. The suffering defied imagination and left a tradition of bad feelings, changing politics in South America forever. This is the definitive work on the Triple Alliance War. Thomas L. Whigham examines key personalities and military engagements while exploring the effects of the conflict on individuals, Paraguayan society, and the continent as a whole. The Road to Armageddon is the first book utilize a broad range of primary sources and materials, including testimony from the men and women who witnessed the war first-hand.